Novel Method for Extraction of Lignin Cellulose & Hemicellulose from Pinus roxburghii Needles (American Journal of Innovation in Science and Engineering, 2023)
Lignocelluloses are becoming a major area of attraction for the researchers for their sustainability and cost effectiveness. The ease of functionalization of these matrices, remarkable physical and chemical properties, and tunable functional sites make them incredible materials for tissue engineering and drug delivery among other applications. The present study focuses on extracting biomaterials lignin, cellulose and hemicellulose from the Pinus roxburghii (PR) needles following a single source procedure. A green chemistry approach ensures minimum wastage with maximum output from the raw material.The Pinus roxburghii (PR) needles were collected from the local area, washed thoroughly, dried in the oven at 45°C for few days and grounded to powder. The PR powder was subjected to treatment with acetic acid: formic acid in the ratio of 1gm/10ml mixture at different concentration to study the yields, for 1hr at low temperature followed by 3hrs treatment at 110°C. The concentrated mother liquor thus obtained was filtered, diluted and left undisturbed for 48h. Lignin precipitates obtained were separated and dried in oven at 30°C. Subsequently, the residue from the extracted lignin was washed to neutralise the pH and dried in oven. By using 5% NaOH reflux treatment at 90-110°C for 3h, hemicellulose was recovered from the pre-treated pine needles mother liquor from which the lignin had been extracted. The mother liquor was treated with ethanol and acetic acid to precipitate hemicellulose in the freezer. The residue obtained after the removable of hemicellulose was washed again to and subsequently bleached to get cellulose. An excellent yield of the desired products was obtained. The extracted products were subjected to characterization studies namely FTIR and HRMS etc to get evidence for successful extraction. The analysis revealed that the PR leaves contained about 1.5wt% to 3.0wt% lignin, 15-30wt% hemicellulose and rest is cellulose.Further, aim is to use the extracted material to prepare the nano-hydrogels for the drug delivery and other applications.